Characterization of the crystal and magnetic structures of the mixed-anion coordination polymer Cu(HCO2)(NO3)(pyz) {pyz = Pyrazine} by X-ray diffraction, ac magnetic susceptibility, dc magnetization, muon-spin relaxation, and spin dimer analysis. - Manson, J; Lancaster, T; Schlueter, J; Blundell, S; Brooks, M; Pratt, F; Nygren, C; Koo, H; Dai, D; Whangbo, M (2007)
The mixed-anion coordination polymer Cu(HCO2)(NO3)(pyz) was synthesized, its crystal structure was determined by X-ray diffraction, and its magnetic structure was characterized by ac susceptibility, dc magnetization, muon-spin relaxation, and spin dimer analysis. The crystal structure consists of five-coordinate Cu2+ ions that are connected through syn-anti bridging mu-HCO2- and mu-pyz ligands to form a highly corrugated two-dimensional layered network. Bulk magnetic measurements show a broad maximum in chi(T) at 6.6 K. The HCO2- and pyz ligands mediate ferromagnetic and antiferromagnetic spin exchange interactions between adjacent Cu2+ ions with the spin exchange parameters J/kB = 8.17 and -5.4 K, respectively (H = -JSigmaSi x Sj). The muon-spin relaxation data show a transition to a long-range magnetic ordering below TN = 3.66(3) K. For T < TN, the M(H) and chi'ac measurements provide evidence for a field-induced spin-flop transition at 15.2 kOe. That Cu(HCO2)(NO3)(pyz) undergoes a long-range magnetic ordering is an unexpected result because the one-dimensional Cu(NO3)2(pyz) and three-dimensional Cu(HCO2)2(pyz) compounds display linear chain antiferromagnetism with no long-range magnetic ordering down to 2 K.